2012
DOI: 10.1371/journal.pone.0050929
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Glycoprotein Enrichment by Concanavalin A Enabled Identification of Novel Membrane Autoantigen Synaptotagmin-1 in Equine Recurrent Uveitis

Abstract: Complete knowledge of autoantigen spectra is crucial for understanding pathomechanisms of autoimmune diseases like equine recurrent uveitis (ERU), a spontaneous model for human autoimmune uveitis. While several ERU autoantigens were identified previously, no membrane protein was found so far. As there is a great overlap between glycoproteins and membrane proteins, the aim of this study was to test whether pre-enrichment of retinal glycoproteins by ConA affinity is an effective tool to detect autoantigen candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The functional meaning of interspecific differences regarding the physiological expression of α-internexin needs to be clarified in follow-up studies. Knowledge of these expression patterns is also relevant under pathological conditions, e.g., in a spontaneous equine model of autoimmune uveitis where vitreal IgM autoantibodies target NF-M in neuronal processes of the retina (Swadzba et al, 2012).…”
Section: "Starburst" Amacrine Cellsmentioning
confidence: 99%
“…The functional meaning of interspecific differences regarding the physiological expression of α-internexin needs to be clarified in follow-up studies. Knowledge of these expression patterns is also relevant under pathological conditions, e.g., in a spontaneous equine model of autoimmune uveitis where vitreal IgM autoantibodies target NF-M in neuronal processes of the retina (Swadzba et al, 2012).…”
Section: "Starburst" Amacrine Cellsmentioning
confidence: 99%
“…The S‐antigen, a major autoantigen in human medicine, resulted in a significantly lower number of uveitis cases when used to experimentally induce uveitis in horses (Deeg et al, 2004b). Two additional retinal autoantigens have been detected more recently: cellular retinaldehyde‐binding protein (cRALBP), part of the rod and cone visual cycle, and synaptotagmin‐1, a protein integral to synaptic vesicle membranes (Deeg et al, 2006a; Swadzba et al, 2012). Deeg et al (2002b) revealed that disease severity, as well as the T cell response, varied amongst the uveitis cases following experimental induction with IRBP.…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…The combination of active downscaling in damaged RMG and release of NF-M fragments into the adjacent vitreous might cause this combination of high vitreal occurrence and low retinal levels of NF-M ( 130 ). A further novel membrane-bound autoantigen, synaptotagmin-1, was identified with decreased expression in ERU ( 131 ), which might be a result of active downscaling of this protein in the retina through impaired neurotransmitter release in ERU. Since Synaptotagmin-1 is also expressed in the pineal gland, and pinealitis is known to concurrently develop in ERU horses ( 132 ), synaptotagmin-1 might play a role in pineal immunopathology in ERU ( 131 ).…”
Section: Target Organmentioning
confidence: 99%
“…A further novel membrane-bound autoantigen, synaptotagmin-1, was identified with decreased expression in ERU ( 131 ), which might be a result of active downscaling of this protein in the retina through impaired neurotransmitter release in ERU. Since Synaptotagmin-1 is also expressed in the pineal gland, and pinealitis is known to concurrently develop in ERU horses ( 132 ), synaptotagmin-1 might play a role in pineal immunopathology in ERU ( 131 ). Whether these IgM-targeted retinal antigens qualify as autoantigen targets for ERU, however, remains to be proven in further studies.…”
Section: Target Organmentioning
confidence: 99%